ANALYSIS OF THE DIAGNOSTIC VALUE OF MAGNETIC RESONANCE COMPUTER TOMOGRAPHY AND POSITRON EMISSION COMPUTER TOMOGRAPHY WITH 18F-FDG IN IDENTIFICATION OF SPINAL AND PELVIC BONE METASTASES - A. V. Laryukov; R. Sh. Hasanov; Z. A. Afanasyeva; E. K. Laryukova (Сибирский онкологический журнал)
Background. The treatment outcomes for non-small cell lung cancer (NSCLC) depend on the tumor stage and treatment strategy. The imaging techniques play a significant role in the diagnosis, staging and choice of appropriate treatment for NSCLC.Purpose of the study: сomparison of the diagnostic capabilities of magnetic resonance imaging (MR) and positron emission computed tomography to select the optimal approaches to early detection of spinal and pelvic bone metastases.Material and Methods. The treatment outcomes were analyzed in 71 patients with NSCLC. Spinal and pelvic bone metastases were detected in 24 patients using magnetic resonance imaging (MRI) and positron emission computed tomography (PET/CT). Multiple bone lesions were the most common. A total of 69 metastatic lesions were identified. To compare the capabilities of diagnostic techniques, all patients underwent PET/CT with 18F-FDG, and MRI of the spine and pelvic bones using diffused-weighted images (DWI). Statistical data processing included the calculation of the sensitivity, specificity and diagnostic accuracy of the above techniques.Conclusion. The comparative analysis of the capabilities of modern high-tech diagnostic techniques (PET/CT with 18F-FDG and MRI of the spine and pelvic bones with DWI) in early detection of bone metastases in patients with NSCLC, PET/CT with 18F-FDG showed the greatest diagnostic value. However, taking into account the high sensitivity and specificity of MRI with DVI in detection of bone metastases and limited availability of PET/CT for patients, MRI with DVI is recommended to exclude bone metastases.